2022
DOI: 10.1088/1367-2630/ac87c8
|View full text |Cite
|
Sign up to set email alerts
|

Generation of terahertz radiation with fractional or integer OAMs from a fractional-order vortex two-color field

Abstract: This paper investigates the generation of the ultra-broadwidth (0.1-30 THz) terahertz (THz) radiation carrying fractional/integer orbital angular momentums (OAMs) via the interaction of the two-color (ω0 and 2ω0) laser field carrying initial fractional topological charges (TCs) with air in a moderate pump intensity regime (20 TW/cm2<Ipump<50 TW/cm2). The two four-wave mixing (FWM) processes (i.e., ω0+ω′0-2ω0→ωTHz and 2ω0-ω0-ω′0→ωTHz) are responsible for THz generation. The two processes can produce two T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(1 citation statement)
references
References 58 publications
(139 reference statements)
0
1
0
Order By: Relevance
“…[23] In 2022, Wang et al used a fractional-order vortex two-color field to generate THz fractional vortex beam in simulation. [24] Furthermore, it is demonstrated that THz vortex beams can be used in communication [20,25] and magnetic excitations. [26] Nevertheless, THz vortex beam has the same disadvantages as optical vortex beam in which ring radius increases with the topological charge number increasing.…”
Section: Introductionmentioning
confidence: 99%
“…[23] In 2022, Wang et al used a fractional-order vortex two-color field to generate THz fractional vortex beam in simulation. [24] Furthermore, it is demonstrated that THz vortex beams can be used in communication [20,25] and magnetic excitations. [26] Nevertheless, THz vortex beam has the same disadvantages as optical vortex beam in which ring radius increases with the topological charge number increasing.…”
Section: Introductionmentioning
confidence: 99%